LOYALITAS MEREK DI SOCIAL COMMERCE OLEH PENGGUNA AKUN TWITTER APPLE DI INDONESIA - Anshar, Abdul Rahman Lubis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This study aims to determine the effect of Brand loyalty In Social Commerce by Apple Twitter Account Users in Indonesia. The sample used in this study is the user Twitter account who has followed Twitter account Apple Indonesia. This research method using questionnaire as a research instrument. Questionnaires were successfully analyzed as many as 100 questionnaires. Sampling technique used is non-probability sampling. SEM-based variants, Partial Least Square (PLS) is used as a method of analysis to determine the effect of the variables involved. The results showed that self congruence, information quality, and interactivity that significantly influence brand loyalty. The implications of this research, the management company that owns the brand pages on social media need to increase self congruence, information quality, and interactivity so as to increase customer brand loyalty.Keywords: Social Commerce, Brand Loyalty, Quality Relations, Social Media, Microblog